An overview and update of low-impact developments (LIDS) in Thunder Bay - Wells, Tyler (My University, 2023)
Climate change is accelerating at a rapid pace across the globe and with this, flooding in urban environments is also increasing. This means that there is and will be an increasing need for alternative methods of stormwater management. Low impact developments (LIDs) are a green way that cities can manage their stormwater. Thunder Bay has been incorporating LIDs into the stormwater management process to improve its ability to handle urban runoff and prevent flooding. This paper will provide an overview of the LIDs within the city and describe how they function and their benefits. This information can be used to further understand the benefits of LIDs and how they can be implemented in various cities.
Keywords: Climate change; Flooding; Low-impact developments; Rain gardens; Storm events; Urban water management